Facile synthesis of pure phase γ-AlOOH and γ-Al2O3 nanofibers in a recoverable ionic liquid via a low temperature route. Issue 127 (11th December 2015) - Cai, Yuan; Huang, Huihui; Wang, Lei; Zhang, Xiaojun; Yuan, Yuewei; Li, Rui; Wan, Hui; Guan, Guofeng
Abstract : Mesoporous γ-AlOOH and γ-Al2 O3 with fibrous morphology were successfully synthesized by an ionic liquid ([OMim]Br) assisted low temperature precipitation method using aluminum nitrate and ammonia as aluminum source and precipitant, respectively. Abstract : Mesoporous γ-AlOOH and γ-Al2 O3 with fibrous morphology were successfully synthesized by an ionic liquid ([OMim]Br) assisted low temperature precipitation method using aluminum nitrate and ammonia as aluminum source and precipitant, respectively. The samples were characterized by XRD, TG, FT-IR, TEM, and N2 adsorption–desorption technique. The results showed that the concentration of [OMim]Br had a significant effect on the phase, porous structure, and morphology of γ-Al2 O3 due to the strong interactions between [OMim]Br and γ-AlOOH. High purity γ-AlOOH was synthesized at 0.2 M [OMim]Br and γ-Al2 O3 with a specific surface area of 243.53 m 2 g −1, pore volume of 0.68 cm 3 g −1, and average pore size of 11.10 nm was obtained after calcination. Furthermore, the recyclability of [OMim]Br was investigated. The recovery rate of [OMim]Br could reach 95.0 wt%, and the recycled [OMim]Br still had effects on the synthesis of γ-AlOOH and γ-Al2 O3 .